Cell response in bronchoalveolar lavage fluid after sulfur dioxide exposure. - Sandstrom, T.; Stjernberg, N.; Andersson, M. C.; Kolmodin-Hedman, Birgitta; Lindstrom, K.; Rosenhall, L. (Scandinavian Journal of Work, Environment & Health, 1989)
Environmental chamber exposure and bronchoalveolar lavage (BAL) were used to study the dose-response relationship between short-term exposure to sulfur dioxide (SO2) and inflammatory reactions in the human lung as reflected in BAL fluid. Healthy subjects were exposed to 10, 13, 20, or 30 mg/m3 for 20 min. BAL was performed several weeks preexposure and 24 h postexposure. Mast cells, lymphocytes, lysozyme positive macrophages, and the total number of macrophages were significantly increased after SO2 exposure. A dose-dependent increase in the cell response in BAL fluid was observed after exposure to 10-20 mg/m3, but no further increase was detected after 30 mg/m3. Inflammatory cell response was found in BAL fluid at SO2 levels that occur in industrial indoor environments worldwide, and cell response to SO2 was also seen below the short-term exposure limit of Sweden and many other countries (13 mg/m3).